Accurate tuning of rare earth metal–organic frameworks with unprecedented topology for white-light emission. Issue 4 (20th December 2019) - Wang, Yutong; Zhang, Kai; Wang, Xiaokang; Xin, Xuelian; Zhang, Xiurong; Fan, Weidong; Xu, Ben; Dai, Fangna; Sun, Daofeng
Abstract : An unprecedented three-dimensional (3D) (3, 4, 5)- c zkf topological framework (UPC-38 ) with one-dimensional (1D) chain secondary building units exhibits strong white light emission. Abstract : A series of isostructural rare-earth metal–organic frameworks (RE-MOFs), namely [RE(L-X)(H2 O)]·2DMF n (UPC-38, RE = Eu, Tb, X = H, F, Cl, NH2, CH3, OCH3 ; L = [1, 1′:3′, 1′′-terphenyl]-4, 4′′, 5′-tricarboxylic acid) have been successfully synthesized under solvothermal conditions. Single-crystal X-ray diffraction analysis shows that UPC-38 is an unprecedented three-dimensional (3D) (3, 4, 5)- c zkf topological framework with one-dimensional (1D) chain secondary building units. Different functional groups can be attached to the ligand (L), and the effects of the different functional groups on the fluorescence intensity, emission wavelength and quantum yield of UPC-38 were systematically studied. It was found that the introduction of an amino group causes the emission wavelength to red shift significantly, while that of other groups causes slight effects on the emission wavelengths. UPC-38(Eu)-H and UPC-38(Tb)-H without modified functional groups in these twelve crystals exhibit the highest quantum yield ratios of 16.64% and 28.06%, respectively. Remarkably, by adjusting the ratio of Eu 3+ to Tb 3+ and the L-OCH3 3+ ligand with the strongest blue emission, a series of double-doped rare-earth metal–organic frameworks, UPC-38(Eu x Tb1− x )-OCH3 (0 ≤ x ≤ 1), are successfully acquired. The calculated CIE coordinates of UPC-38(Eu)-OCH3 and UPC-38(Tb)-OCH3 are (0.50, 0.28) and (0.23, 0.45), respectively. It is exciting that a white light emitting material, UPC-38(Eu0.34 Tb0.66 )-OCH3, can be successfully obtained through careful tuning of the Eu 3+ /Tb 3+ ratio in the framework. The CIE coordinate is (0.335, 0.325), which is very close to the standardized value of (0.333, 0.333).